PT Madina Solusi Indonesia Fiber to the Home (FTTH) Perancangan menggunakan GPON Teknologi (Studi Kasus : PT. Madina Solusi Indonesia): Penelitian - Miftah Farid; Singgih Prastyo Nugroho (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research focuses on designing a Fiber To The Home (FTTH) network in Perumnas Condongcatur, Yogyakarta, with Gigabit Capable Passive Optical Network (GPON) technology. in the area. The project is driven by the increasing need for reliable internet services according to the eligibility standards of the Indonesia Digital Network (IDN) program. This research includes results according to technical, economic, and social aspects related to FTTH design. The use of Google Earth and Opticsystem software resulted in attenuation of less than -28dBm for attenuation feasibility measurements. The results of this gpon-based infrastructure design are expected to provide a solution for PT Madina Solusi Indonesia in providing internet services that support digital transformation in the region.